Pemanfaatan Media Sosial Untuk Membentuk Personal Branding Sebagai Bentuk Komunikasi Bisnis Studi Kasus : Shella Saukia (SS) - Hutahaean, Linda Sariana; Silaban, Yusuf Arnawi; Sirait, Nathanael; Sinaga, Erlina Tiveen F; Daniel Purba, Pransisko; Kasih Zai, Berkat; Windu Sihombing, Nadya; Sitorus P, Lampola (Jurnal Ilmu Sosial Dan Politik, 2025)
The development of social media has led people to increasingly use these platforms to build their self-image in modern business. This study aims to analyze how Shella Saukia utilizes social media to build a personal brand that supports her business activities. This research used a qualitative approach with a case study method, analyzing content taught on various digital platforms. The results show that maintaining consistency in content themes, conveying messages clearly, and aligning personal identity and professional image significantly helps strengthen relationships with audiences, increase public trust, and support strategic and sustainable business communication and performance.